Dynamic roles of inflammasomes in inflammatory tumor microenvironment - Jeong-Hoon Jang (Nature Portfolio, 2021)
Abstract The inflammatory tumor microenvironment has been known to be closely connected to all stages of cancer development, including initiation, promotion, and progression. Systemic inflammation in the tumor microenvironment is increasingly being recognized as an important prognostic marker in cancer patients. Inflammasomes are master regulators in the first line of host defense for the initiation of innate immune responses. Inflammasomes sense pathogen-associated molecular patterns and damage-associated molecular patterns, following recruitment of immune cells into infection sites. Therefore, dysregulated expression/activation of inflammasomes is implicated in pathogenesis of diverse inflammatory disorders. Recent studies have demonstrated that inflammasomes play a vital role in regulating the development and progression of cancer. This review focuses on fate-determining roles of the inflammasomes and the principal downstream effector cytokine, IL-1β, in the tumor microenvironment.